2016
DOI: 10.18632/oncotarget.13625
|View full text |Cite
|
Sign up to set email alerts
|

Cancer initiating-cells are enriched in the CA9 positive fraction of primary cervix cancer xenografts

Abstract: Numerous studies have suggested that Cancer Initiating Cells (CIC) can be identified/enriched in cell populations obtained from solid tumors based on the expression of cell surface marker proteins. We used early passage primary cervix cancer xenografts to sort cells based on the expression of the intrinsic hypoxia marker Carbonic Anhydrase 9 (CA9) and tested their cancer initiation potential by limiting dilution assay. We demonstrated that CICs are significantly enriched in the CA9+ fraction in 5/6 models stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…CA9 was found to be overexpressed in many cancers and suggested as a common feature of cancer cells 30 , 33 - 42 . It indicated that CA9 was required for tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…CA9 was found to be overexpressed in many cancers and suggested as a common feature of cancer cells 30 , 33 - 42 . It indicated that CA9 was required for tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, survival of microenvironmental stresses including hypoxia and acidosis depend on the enzyme activity of the catalytic domain as described above. It is believed that metastatic lesions are generated by cancer stem cells and CA IX expression was shown to be associated with stem-like phenotype [80, 81].…”
Section: Ca IX Contributions To Key Steps Of Cancer Developmentmentioning
confidence: 99%
“…It is known that CtBPs promote the formation of SCLC cells [35,40,49] and CAIX has also been clearly demonstrated to be an important marker of cells with a stem cell-like phenotype [66,78]. In this light, we investigated the role of glycolysis-CtBP-NADH axis in the formation of SCLC cells in MCF-7 breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%